Model Transformasi Sosial Partisipatif Berbasis Nilai: Integrasi Literasi Qur’ani, Program Lingkungan, dan Keselamatan Publik dalam Pemberdayaan Desa - Nurilah Nurilah; Andini Uzlifah; Muammir Muammir; Farhan Farhan (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
This study reconstructs a normative mediation mechanism in participatory social transformation by examining how value internalization shapes collective ecological and social practices in a rural Muslim community. The research employed a qualitative approach using an exploratory case study design conducted in Haurgeulis District, Indramayu Regency. Data were collected from 16 key informants selected purposively, consisting of religious leaders, youth, Qur’anic literacy program managers, and community members actively involved in environmental and safety initiatives. Data collection methods included participatory observation, in-depth interviews, and document analysis. The data were analyzed thematically through iterative processes of coding, categorization, and interpretative synthesis. The findings indicate that Qur’anic literacy functions as a normative driver that legitimizes and strengthens social participation by fostering collective moral awareness. The integration of religious values with ecological practices and community safety initiatives encourages a shift from administrative compliance toward sustained participatory consciousness. Community engagement not only enhances environmental management and collective vigilance but also reinforces social cohesion and youth educational aspirations. The study proposes a relational-cyclical model of participatory social transformation based on three interrelated pillars: value internalization, collective practice, and social cohesion reinforcement. Theoretically, this research contributes to community empowerment literature by positioning Qur’anic literacy as a normative mediator in the integration of social programs. Practically, the proposed model offers a conceptual framework for developing value-based and sustainability-oriented village empowerment initiatives.